Optimization and classification control of permanent basic farmland based on quality classification - Wei Wang; Yiling Chen; Kun Liu; Yingchun Dang; Guilong Li; Liangyou Wen; Yun Cao (Frontiers in Environmental Science, 2024)
Permanent basic farmland plays an important role in stabilizing agricultural production and ensuring national food security. Therefore, it is necessary to reasonably delineate and control permanent basic farmland. This article is based on the idea of classifying the quality of cultivated land resources, combined with the rules for the delineation of permanent basic farmland, and from the perspective of the synergy of “suitability-connectivity-stability” of cultivated land, a indicator system is constructed. Application of suitability, connectivity, and stability evaluation methods. Taking Zhangshu City, Jiangxi Province as an example, the status of cultivated land resources is comprehensively evaluated, and permanent basic farmland is optimized and graded for protection. The results show that: (1) the arable land in Zhangshu City is mainly of medium suitability, medium continuity and high stability. (2) Zhangshu City is divided into 43218.80 hm2 of permanent basic farmland, accounting for 79.35% of the total area of cultivated land. (3) Control and partition permanent basic farmland into three categories: core protected areas for permanent basic farmland, quality improvement areas, and key transformation areas. The above results indicate that this evaluation has a supportive role in supporting the spatial optimization and hierarchical management of permanent basic farmland, and is of great significance for the unified management of natural resources.